The Relationship Between Food Craving, Appetite-Related Hormones and Clinical Parameters in Bipolar Disorder - Platzer, Martina (Nutrients, 2020)
Obesity and weight gain in bipolar disorder (BD) have multifactorial underlying causes such as medication side effects, atypical depressive symptomatology, genetic variants, and disturbances in the neuro-endocrinal system. Therefore, we aim to explore the associations between food craving (FC), clinical parameters, psychotropic medication, and appetite-related hormones. In this cross-sectional investigation, 139 individuals with BD and 93 healthy controls (HC) completed the food craving inventory (FCI). In addition, blood samples (including leptin and acylated ghrelin) were analyzed and sociodemographic and anthropometric data were collected. Individuals with BD reported higher frequencies of total FC as well as craving for fat and fast food than HC. Additionally, we found a significant negative correlation between FC and ghrelin levels in BD. Smokers with BD reported significantly more craving for high fat foods than non-smokers. Age was significantly associated with FC independent of group. Individuals with BD taking olanzapine and quetiapine reported higher frequencies of craving for sweet food, while patients currently taking lithium reported less total FC compared to those without lithium therapy. Likewise, patients currently taking valproate reported less total FC and less craving for sweets than those not taking valproate. FC appears to be of clinical relevance in individuals with BD. Contrary to previous data, this does not seem to be a female phenomenon only and might encompass more than the specific craving for carbohydrates. Although due to the cross sectional design, causality cannot be determined, the association between depressive symptomatology and fast food craving warrants further research.